"IMPLICATIONS OF ARTICLE 477 OF THE 2023 CRIMINAL CODE ON LAW ENFORCEMENT OF THEFT WITH COMPARATIVE ANALYSIS WEIGHTING WITH ARTICLE 363 OF THE OLD CRIMINAL CODE" - Andi Herman Yusuf; Muhammad Natsir; Elvi Susanti Syam; Sunardi Purwanda; Muhammad Sabir (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The enactment of the 2023 Criminal Code (KUHP) brought significant changes to the regulation of the crime of aggravated theft, particularly through Article 477 of the 2023 Criminal Code, which replaced Article 363 of the old Criminal Code. This change is not only editorial in nature, but also has implications for the construction of criminal elements and law enforcement practices. This study aims to analyze the implications of the application of Article 477 of the 2023 Criminal Code on the enforcement of the law on aggravated theft and compare it with the provisions of Article 363 of the old Criminal Code. The research method used is normative legal research with a legal approach and a comparative approach, supported by primary, secondary, and tertiary legal materials. The results of the study indicate that there are differences in the regulation of aggravating elements and the systematics of punishment that have the potential to affect the investigation process, prosecution, and judges' considerations in issuing decisions. In addition, the implementation of Article 477 of the 2023 Criminal Code still faces challenges in terms of norm interpretation and the readiness of law enforcement officers. This study concludes that a comprehensive understanding and implementation guidelines are needed so that the implementation of the new provisions can guarantee legal certainty and the effectiveness of law enforcement against the crime of aggravated theft.